The variations in volatile organic compounds based on the policy change for Omicron in the traffic hub of Zhengzhou - B. Zhang; B. Zhang; D. Zhang; D. Zhang; Z. Dong; Z. Dong; X. Song; X. Song; R. Zhang; R. Zhang; X. Li; X. Li (Atmospheric Chemistry and Physics)
Online volatile organic compounds (VOCs) were monitored before and after the Omicron policy change at an urban site in polluted Zhengzhou from 1 December 2022 to 31 January 2023. The characteristics and sources of VOCs were investigated. The daily mean concentrations of PM2.5 and total VOCs (TVOCs) ranged from 53.5 to 239.4 µg m−3 and 15.6 to 57.1 ppbv, respectively, with mean values of 111.5 ± 45.1 µg m−3 and 36.1 ± 21.0 ppbv, respectively, throughout the period. Two severe pollution events (designated as case 1 and case 2) were identified in accordance with the National Ambient Air Quality Standards (NAAQS) (China's National Ambient Air Quality Standards (NAAQS) from 2012). Case 1 (5 to 10 December PM2.5 daily mean = 142.5 µg m−3) and case 2 (1 to 8 January PM2.5 daily mean = 181.5 µg m−3) occurred during the infection period (when the policy of “full nucleic acid screening measures” was in effect) and the recovery period (after the policy was canceled), respectively. The PM2.5 and TVOC values for case 2 are, respectively, 1.3 and 1.8 times higher than those for case 1. The precise influence of disparate meteorological circumstances on the two pollution incidents is not addressed in this study. The results of the positive matrix factor modeling demonstrated that the primary source of VOCs during the observation period was industrial emissions, which constituted 32 % of the total VOCs, followed by vehicle emissions (27 %) and combustion (21 %). In case 1, industrial emissions constituted the primary source of VOCs, accounting for 32 % of the total VOCs. In contrast, in case 2, the contribution of vehicular emission sources increased to 33 % and became the primary source of VOCs. The secondary organic aerosol formation potential for case 1 and case 2 were found to be 37.6 and 65.6 µg m−3, respectively. In case 1, the largest contribution of SOA formation potential (SOAP) from industrial sources accounted for the majority (63 %; 23.8 µg m−3), followed by vehicular sources (18 %). After the end of the epidemic and the resumption of productive activities in the society, the difference in the proportion of secondary organic aerosol (SOA) generated from various sources decreased. Most of the SOAP came from solvent use and fuel evaporation sources, accounting for 32 % (20.9 µg m−3) and 26 % (16.8 µg m−3), respectively. On days with minimal pollution, industrial sources and solvent use remain the main contributors to SOA formation. Therefore, the regulation of emissions from industry, solvent-using industries, and motor vehicles needs to be prioritized to control the PM2.5 pollution problem.